Charisma, Tradition, and Rationality: The Authority of Teungku in Maintaining Social Order - Rahmawati, Mimi; Ikramatoun, Siti (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
The study examines the role of Teungku—local religious leaders in maintaining social order in Gampong Krueng Tuynong, Aceh Jaya. Drawing on Max Weber’s theory of authority, the study analyzes how the three types of authority—traditional, charismatic, and legal-rational—interact and function synergistically within informal religious leadership. Using a qualitative narrative method, data were collected through in-depth interviews, field observations, and documentation. The findings indicate that Teungku gains legitimacy through lineage, moral charisma, and involvement in village governance structures. Their leadership, rooted in cultural heritage and ethical example, positions them as mediators, educators, and guardians of social harmony. Empirically, this study demonstrates that the stability of post-conflict village social structures can remain stable through informal leadership that is not formally institutionalized, yet holds socially recognized authority. Theoretically, it offers a new synthesis of Weber’s typology by showing that, in local contexts such as Aceh, the three forms of authority do not operate in isolation but instead converge functionally within the figure of the Teungku. Thus, this article contributes to a broader understanding of how informal religious authority can serve as a stabilizing force in communities shaped by layered values, traditions, and local norms.